Sustainable Supply Chain Management in the Quantitative Framework: Developments, Directions and Economic Analysis in Indonesia - Srinita Srinita (International Journal of Supply Chain Management, 2018)
The prime objective of the current study was to investigate the impact of an effective supply chain system on sustainable supply chain management in Indonesia. In addition to that, we have also investigated the impact of information and communication technology on the relationship between the effective supply chain system and sustainable supply chain management. this study adopted PLS SEM to analyze the data. After confirmation of reliability and validity, the SEM was used to analyze the hypothesis. The direct and indirect effect was examined. Indirect effect was examined to check the mediation. In this process, the p-value was considered. While analyzing the data, 0.05 minimum level of p-value was considered to test the hypothesis. According to the direct results, it is shown that all hypothesis has a p-value less than 0.05. Therefore, it accepts H1, H2, H3, H4, H5, H6 and H7 and for all mediation hypothesis, the t-value is above 1.96 and p-value is below 0.05 which accept H8, H9, and H10. Before testing the hypothesis, data reliability and validity was scrutinized. These steps were taken through PLS 3. The results of the study are showing a great deal of agreement with our proposed hypothesis as all of our hypothesis are accepted significantly. The results of the study are will be helpful for policymakers, researchers, and practitioner for formulating policy or carrying out researches on the issue of sustainable supply chain management.